Basic Computer Learning with Unplugged and Plugged Activity - S. Mukaromah; Wahyuni, E. D.; Afandi, M. I. (Future Science)
In this modern era, it is very common that development of Information and Communication Technology (ICT) is very well known. For instance we see many office, learning, or even game application. Whether is it online game or offline game. Many school-age children around 10 to 13 years old, spend their free time to play games. This is not a good habit, because it can make them addict to game and not focus at their study anymore. This impact make them be a end user. Therefore it has to change to make them be creative to create game by their own. It has two method that can be used to drive them be more creative. First step is use unplugged activity and then plugged activity. Unplugged activity is a series of learning computer with no computer. In this series there are 2 games will be played, they are “jumping frog” and “mouse maze”. In this unplugged game student will study about first step to introduce code (basic logic thinking). After student understand the logic thinking of computer they will get plugged activity, which is scratch. At this scratch level the student start to make the basic simple code. This research was done with good effort to provide alternative solutions that school-age student be a creative student.